Germ Cell Responses to Stress: The Role of RNP Granules - Schisa, Jennifer A. (Frontiers in Cell and Developmental Biology, 2019)
The ability to respond to stress is critical to survival for animals. While stress responses have been studied at both organismal and cellular levels, less attention has been given to the effect of stress on the germ line. Effective germ line adaptations to stress are essential to the propagation of a species. Recent studies suggest that germ cells share some cellular responses to stress with somatic cells, including the assembly of RNP granules, but may also have unique requirements. One fundamental difference between oocytes and sperm, as well as most somatic cells, is the long lifespan of oocytes. Since women are born with all of their eggs, oocytes must maintain their cellular quality over decades prior to fertilization. This prolonged meiotic arrest is one type of stress that eventually contributes to decreased fertility in older women. Germ cell responses to nutritional stress and heat stress have also been well-characterized using model systems. Here we review our current understanding of how germ cells respond to stress, with an emphasis on the dynamic assembly of RNP granules that may be adaptive. We compare and contrast stress responses of male gametes with those of female gametes, and discuss how the dynamic cellular remodeling of the germ line can impact the regulation of gene expression. We also discuss the implications of recent in vitro studies of ribonucleoprotein granule assembly on our understanding of germ line responses to stress, and the gaps that remain in our understanding of the function of RNP granules during stress.